RGEC dan Nilai Perusahaan : Studi Empiris pada Bank Syariah di BEI - Yuliana, Elis; Setiawan, Agus (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
The banking industry substantially contributes to and is important to national economic growth. Per the 2014 Islamic Banking Health Law, banks must utilize the RGEC methodology to ascertain whether they operate soundly and sustainably. The results of the RGEC assessment may influence investors' decisions regarding the performance of a given bank. The objective of this research is to ascertain whether the price-to-book value ratio of Islamic banks listed on the Indonesia Stock Exchange during the period 2021-2023 is influenced by the following factors: capital (capital adequacy ratio), earnings (return on assets), good corporate governance (audit committee), and risk profile (BOPO). The sampling technique employed was purposive sampling, which yielded four Islamic banks (Bank Syariah Indonesia, Bank BTPN Syariah, Bank Aladin Syariah, and Bank Panin Syariah). The data analysis strategy employed in this study utilized the SPSS 27 application and Excel. According to this research, investor assessments have not been sufficiently impacted by operational effectiveness, profitability, or the regularity of supervision; instead, capital strength is the primary element impacting the market's impression of the value of Islamic bank firms. In order to boost the company's perceived worth in the eyes of investors, this study advises Islamic banks to give top priority on fortifying the capital structure and upholding adherence to sharia standards.